Model Aplikasi Sistem Informasi Akuntansi Realisasi Anggaran Pada SMAN 1 Banjaran - Regine Berlian Pratama (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2018)
SMAN1 Banjaran which is addressed at Jl. Ciapus No. 7 Bandung Regency is educational institution. At the time of conducting the research, the researcher found the Administration section where there was a treasurer and so on. At SMAN 1 Banjaran it has been computerized, namely by using Microsoft Excel and Word but has not used hyperlink facilities, so that there is a repeat input process. And in making financial reports that are still not in accordance with existing standards. The researcher conducts research in the financial section, namely in the part of the BOS Fund (Student Operational Assistance). So the researcher conducted a study entitled "Accounting Information System Application Model Budget Realization At SMAN 1 Banjaran" In this study the research design used was descriptive analysis, survey, primary data and also secondary data with the type of research used was quantitative, with a system development model use quantitative. The author uses iterations to structure the development of the system. The system design model used by the writer is context diagrams, data flow diagrams, data dictionaries, document flow charts, normalization and entity diagram relationships. Researchers try to make financial statements that are in accordance with the accounting cycle starting from making evidence of transactions, journals, ledgers, balance sheets, and financial statements realization of the budget.